A Musical Note - Steven Ungar (Studies in 20th & 21st Century Literature, 1981)
Frequent references to musical terms in Barthes's writings since 1970 suggest a progression beyond a standard semiological inquiry. A text on the «grain» of the voice, another on música practica, and a third on Romantic song develop a model of figuration Barthes explores actively in the Fragments d'un discours amoureux (A Lover's Discourse) and La Chambre claire.
Keywords: music; musical terms; Barthes; voice; grain of the voice; grain; música practica; Romantic song; Fragments d& #x27; un discours amoureux; A Lover& #x27; s Discourse; La Chambre claire